Antimicrobial Properties of Native Mushrooms of Urban Environment of Bhubaneswar, Odisha - panda, Jiban Jyoti; Nayak, Trupty Pragyan; Dash, Pragyan; Gupta, N (Mushroom Research, 2017)
The present study  was comprised of evaluation of the Ganoderma lucidum, G. tsugae, Phellinus gilvus, P. igniarius, Termitomyces eurrhizus, T. microcarpus, T. medius, T. clypeatus, Macrolepiota procera. M. Clelandii, M. dolichaula, Phallus indusiatus and P. multicolour for bioactive properties. To analyze antimicrobial properties, extracts of different solvents was prepared by using different mushrooms. Total 2 bacteria and 7 fungi were used as test organisms.  Antimicrobial activity was determined by disc diffusion method on Nutrient agar and Sabouraud dextrose agar medium. Most of mushrooms species showed antibacterial and antifungal activity. Most of the mushrooms species studied in the present work exhibited growth inhibition against gram +ve bacteria where as only Ganoderma lucidum Termitomyces eurrhizus and T. microcarpus were found to be active against gram –ve bacteria. Growth inhibition of Colletotrichum was observed from the solvent extracts of Termitomyces eurrhizus, T. microcarpus and Ganoderma tsugae only. This preliminary screening has opened an avenue for the mass scale extraction of active  principle responsible behind the inhibition  activity against gram –ve bacteria.